Postural instability and lower extremity dysfunction in upper motor neuron-dominant amyotrophic lateral sclerosis - Liu, Xiangyi; Chen, Lu; Ye, Shan; Liu, Xiaoxuan; Zhang, Yingshuang; Fan, Dongsheng (Frontiers in Neurology, 2024)
Background: Upper motor neuron-dominant ALS (UMND ALS) is recognized to have early onset and good prognosis, but may have a rapid decline in motor function due to gait instability in the early stage. We investigated changes in lower extremity function in UMND ALS, particularly UMND ALS patients accompanied with postural instability or repeated falls (UMND ALS plus).Results: Among the 2353 ALS patients reviewed, 211 (9.0%) had UMND ALS.UMND ALS had a longer diagnosis delay and restricted symptoms. Although UMND ALS patients had better lower extremity function and strength than matched classic ALS patients on first evaluation, there was no difference in the time of needing assistance or not being able to walk after disease onset. In contrast, UMND ALS plus has severe UMN symptoms and a more rapid decline in motor function. The lower extremity function was no better than that in the matched classic ALS. The prognosis of UMND ALS and UMND ALS plus were significantly better than those of overall ALS.Conclusions: UMND ALS has restricted symptoms but has a rapid decline in lower extremity function in the early stage of the disease. The motor function decline of UMND ALS plus is as fast as classic ALS. Whether these patients represent a distinct subgroup of ALS deserves further investigation.